The challenges faced by conservation practitioners in conservation projects in UNESCO World Heritage Cities / Amira Shahira Shakir and Kartina Alauddin - Shakir, Amira Shahira; Alauddin, Kartina (2019)
Conservation projects normally involve work that cannot accurately predetermine in terms of extent, specification, duration or cost. It was because conservation projects were unique and non-duplicate project which do not have precedent case to study. Thus, the aim of this research is to investigate the challenges faced by the conservation practitioners in conservation project in Malacca and Georgetown. To achieve the aims, data of this research is collected through survey which is by distributing questionnaires to the consultants, contractors and clients to identify challenges faced in conservation project. The method use is questionnaire survey and the responses are from 74 conservation practitioners consist of contractors, consultants and clients who involved in conservation projects in Malacca and Georgetown which listed under UNESCO World Heritage Cities. The data collected were analysed by SPSS version 23. This study identified that the highest mean value for challenges faced by conservation practitioners in conservation projects in Malacca and Georgetown was the expensive construction cost with mean value of 3.31.